Going organic : mobilizing networks for environmentally responsible food production - Lockie, Stewart (CAB books., 2006)
"This book sets out to examine what is really going on in the organic sector - socially and politically. In the process, it debunks a number of apparently common sense beliefs: that organic consumers are wealthy and health extremists; that growth in the industry will inevitably undermine its environmental values; that the mainstream media are antagonistic to organics; that the industry is driven by consumer demand. This book seeks to make a practical contribution to the development of more sustainable food systems by exploring and revealing what it takes to get people involved in organics at each stage of the food chain."--Jacket